PENGARUH PENAMBAHAN NIKEL TERHADAP KEKUATAN TARIK DAN KEKERASAN PADA BESI TUANG NODULAR 50 - Sudarmanto, Sudarmanto (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2016)
Nodular cast iron is the cast iron that has nodular graphite spherical structure distributed in ferrite or pearlite matrix or in both of them. Recently, this material is used widely in industries because its low cost and better performance. The advanced metal industries nowadays have found some new technologies in order to improve the properties of materials. One of them is the addition of another elements into the base metals, such as nickel. The effects of the addition 1wt %, 2wt % and 3wt % nickel into nodular cast iron 50 on tensile and hardness properties were investigated in this study. The experimental results show that the best amount of nickel that added into nodular cast iron is 3% wt, which has the best tensile and hardness properties